2021
DOI: 10.1111/jan.14848
|View full text |Cite
|
Sign up to set email alerts
|

The ROX index can be a useful tool for the triage evaluation of COVID‐19 patients with dyspnoea

Abstract: Aim To assess whether the application of a non‐invasive tool, such as ratio of oxygen saturation (ROX) index, during triage can identify patients with COVID‐19 at high risk of developing acute respiratory distress syndrome (ARDS). Design A multi‐centre, observational, retrospective study. Methods Only COVID‐19 positive patients who required an emergency department evaluation for dyspnoea were considered. The primary objective of the study was to compare the ROX value obtained during triage with the medical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…To the best of our knowledge, only a few papers exploring the correlation between S/F and P/F ratio have been published, and none of them covering COVID-19 patients [3] , [4] , [5] . A recently published study has investigated the correlation between ROX index and P/F ratio in patients with SARS-CoV-2 infection, and the pooled results are consistent with our ones (R = 0.650, p < 0.001) [6] . In all the tests we performed, S/F ratio showed a better correlation than ROX index with P/F ratio; this seems likely related to a wide dispersion of RR values because of the phenomenon of silent hypoxemia, well described in CARDS [7] .…”
supporting
confidence: 91%
“…To the best of our knowledge, only a few papers exploring the correlation between S/F and P/F ratio have been published, and none of them covering COVID-19 patients [3] , [4] , [5] . A recently published study has investigated the correlation between ROX index and P/F ratio in patients with SARS-CoV-2 infection, and the pooled results are consistent with our ones (R = 0.650, p < 0.001) [6] . In all the tests we performed, S/F ratio showed a better correlation than ROX index with P/F ratio; this seems likely related to a wide dispersion of RR values because of the phenomenon of silent hypoxemia, well described in CARDS [7] .…”
supporting
confidence: 91%
“…In our study, the SF ratios after HFNC initiation had an acceptable predictive power (AUC: 0.762 and 0.733). Hu et al [ 23 ] reported that both the ROX index at 6 h and the SF and PF ratios at 6 h are accurate predictors of HFNC failure (AUC: SF ratio of 0.786 and PF ratio of 0.749). Arterial blood gas analysis cannot be performed frequently because COVID-19 patients are isolated in a closed room and the number of healthcare personnel is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood gas analysis cannot be performed frequently because COVID-19 patients are isolated in a closed room and the number of healthcare personnel is limited. Moreover, respiratory rate may be difficult to objectively monitor because the accuracy of respiratory rate measurements by healthcare professionals is suboptimal [ 23 ]. On the other hand, the SF ratio can be calculated by objectively measuring pulse oximetry and FiO 2 ; therefore, we suggest that SF ratios can be a useful tool for predicting intubation in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ROX index, initially designed to predict failure of non-invasive oxygenation in ICU and so utilising only bedside observations, has been applied to patients with COVID-19 in ICU to assess the severity of their hypoxic respiratory failure [17][18][19][20]23] and in correlation with radiological findings [24], with values ranging from 3 [25] to 5.99 [23] (including the non-COVID discriminator of 4.99 [26]) being considered the optimal cut-off to signify requirement for intubation in the ICU setting. By considering ROX as a marker of respiratory response to relative hypoxaemia, our study not only supports the use of this index in predicting adverse outcomes in ICU, but suggests that it may have utility for detecting patients outside of ICU at risk of deterioration with exaggerated respiratory responses to lower degrees of relative hypoxaemia, as it can be derived in a straightforward manner from nursing observations.…”
Section: Discussionmentioning
confidence: 99%